Flexible sensor based on oxide wrinkle structure and preparation method thereof

By preparing flexible sensors based on oxide wrinkle structures, the problem that rigid oxide-based semiconductor active layer cannot be applied to flexible piezoresistive sensors is solved, and a flexible piezoresistive sensor with high precision, high sensitivity and high reliability is achieved, which is suitable for changes in various curved surfaces and shapes.

CN119738069AActive Publication Date: 2025-04-01AVIC XIAN AIRCRAFT IND GRP CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411857720.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-17
Publication Date
2025-04-01
Estimated Expiration
2044-12-17

AI Technical Summary

Technical Problem

The existing rigid oxide-based semiconductor active layer materials cannot meet the application needs of flexible piezoresistive sensors, and the use of metal-based nanomaterials or carbon-based nanomaterials as active layers will lead to reduced sensor sensitivity and damage to non-recoverability.

Method used

Sr3Al2O6 and La-BaTiO3 ceramic targets were prepared by solid phase method, and a heterostructure was formed on the SrTiO3 single crystal substrate combined with pulsed laser deposition technology, and Au electrodes were grown on the PDMS film by water-soluble method and magnetron sputtering method to prepare a flexible sensor with an oxide wrinkle structure.

Benefits of technology

It realizes a flexible piezoresistive sensor with high accuracy, high sensitivity and high reliability, which can adapt to various curved surfaces and shapes and is suitable for applications in compact designs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119738069A_ABST
    Figure CN119738069A_ABST
Patent Text Reader

Abstract

The invention discloses a flexible sensor based on an oxide wrinkle structure and a preparation method of the flexible sensor. The preparation method comprises the following steps: respectively preparing a Sr3Al2O6 target material and a La-BaTiO3 target material by adopting a solid phase method; the preparation method comprises the following steps: preparing a La-BaTiO3 / Sr3Al2O6 / SrTiO3 heterostructure on an SrTiO3 single crystal substrate by using a Sr3Al2O6 target material and a BaTiO3 target material by adopting a pulse laser deposition technology; a water dissolving method is adopted, a polydimethylsiloxane (PDMS) film is electrostatically adsorbed on the La-BaTiO3 / Sr3Al2O4 / SrTiO3 heterostructure, a La-BaTiO3 thin film in the structure is stripped, and a La-BaTiO3 / PDMS heterostructure is prepared; growing a gold (Au) electrode on the La-BaTiO3 / PDMS heterostructure by adopting a magnetron sputtering method, and preparing to obtain an Au / PDMS / La-BaTiO3 heterostructure; the other PDMS film is attached to the surface of the Au electrode with the Au / PDMS / La-BaTiO3 heterostructure by means of electrostatic adsorption for packaging, and the piezoresistive sensor with the PDMS / Au / La-BaTiO3 / PDMS heterostructure is prepared. The preparation method is high in process controllability, and the prepared flexible piezoresistive sensor has the characteristics of high precision, high sensitivity and high reliability; the flexible piezoresistive sensor can adapt to changes of various curved surfaces and shapes, and is wide in application range.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of flexible sensor technology, but is not limited to it, and in particular to a flexible sensor based on an oxide wrinkle structure and a preparation method thereof. Background Art

[0002] As an important component of sensors, piezoresistive sensors are widely used in aviation, chemical industry, navigation, power and medical fields. The device can convert pressure information such as force, air pressure and hydraulic pressure into electrical signals. Piezoresistive sensors are mainly composed of three parts: active layer, electrode and packaging layer. The active layer, as the core of the piezoresistive sensor, needs to show obvious changes in resistance when subjected to pressure. Oxide-based semiconductors, as typical active layer materials, have been widely used in piezoresistive sensors due to their excellent piezoresistance coefficient.

[0003] However, with the continuous development of integrated, miniaturized and complex portable detection equipment, the existing rigid or oxide-based semiconductor active layers grown on rigid substrates can no longer meet the flexible application requirements of piezoresistive sensors. The current solution is to use metal-based nanomaterials or carbon-based nanomaterials as active layers. Although resistance adjustment can be achieved through percolation theory, tunneling effect and other phenomena, the use of low-resistance materials will reduce the sensitivity of the sensor, thereby increasing the probability of irreversible damage.

[0004] Therefore, how to apply rigid piezoresistive active layer materials to the preparation of flexible devices will be an important breakthrough in optimizing the performance of flexible piezoresistive sensors in the future. Summary of the invention

[0005] Purpose of the present invention: In order to solve the above-mentioned technical problems, the embodiments of the present invention provide a flexible sensor based on an oxide wrinkle structure and a preparation method thereof, so as to solve the problem that the existing rigid piezoresistive active layer materials cannot be applied to flexible piezoresistive sensors, and to solve the problem that the existing solutions using metal-based nanomaterials or carbon-based nanomaterials as active layers will cause the sensor sensitivity to decrease, thereby increasing the probability of irreversible damage.

[0006] Technical solution of the present invention: In a first aspect, an embodiment of the present invention provides a method for preparing a flexible sensor based on an oxide wrinkle structure, the method comprising the following steps:

[0007] Step 1: Prepare Sr3Al2O6 ceramic target by solid phase method;

[0008] Step 2: Prepare La using solid phase method 3+ Ion-doped BaTiO3 ceramic target, namely La-BaTiO3 ceramic target;

[0009] Step 3: Using pulsed laser deposition technology, on a SrTiO3 single crystal substrate with a (100) orientation, a "La-BaTiO3 / Sr3Al2O6 / SrTiO3" heterostructure is prepared according to the Sr3Al2O6 ceramic target and the La-BaTiO3 ceramic target;

[0010] Step 4: using a water-soluble method, electrostatically adsorbing a polydimethylsiloxane (PDMS) film onto the "La-BaTiO3 / Sr3Al2O6 / SrTiO3" heterostructure, peeling off the La-BaTiO3 film in the "La-BaTiO3 / Sr3Al2O6 / SrTiO3" heterostructure, and preparing a "La-BaTiO3 / PDMS" heterostructure with a wrinkled structure;

[0011] Step 5: growing a gold Au electrode on the "La-BaTiO3 / PDMS" heterostructure with a wrinkled structure by a magnetron sputtering method to prepare a "PDMS / La-BaTiO3 / Au" heterostructure;

[0012] Step 6: Attach another PDMS film to the Au electrode surface of the "Au / La-BaTiO3 / PDMS" heterostructure by electrostatic adsorption to encapsulate it, so as to obtain a piezoresistive sensor of the "PDMS / Au / La-BaTiO3 / PDMS" heterostructure.

[0013] Optionally, in the method for preparing a flexible sensor based on an oxide wrinkle structure as described above, step 1 comprises:

[0014] Step 1.1, accurately weigh SrCO3 powder and Al2O3 powder according to the molar ratio of Sr to Al element of 3:2 as raw material 1;

[0015] Step 1.2, weighing ball stone and alcohol according to the mass ratio of raw material 1: ball stone: alcohol = 1:2:2, mixing, ball milling, and sieving, placing the sieved mixed liquid in a constant temperature drying oven for drying, and preparing a raw material 1 with uniform powder mixing; wherein the drying temperature is 80°C and the drying time is 24h;

[0016] Step 1.3, putting the raw material 1 mixed with the powder into a crucible, and calcining it in an air atmosphere to synthesize Sr3Al2O6 powder; wherein the calcination temperature is 1200°C and the holding time is 4h;

[0017] Step 1.4, according to the mass ratio of Sr3Al2O6 powder: ball stone: alcohol = 1:2:2, weigh the ball stone and alcohol, mix, ball mill, and sieve, and place the sieved mixed solution in a constant temperature drying oven for drying to prepare Sr3Al2O6 fine powder after powder refinement; wherein the drying temperature is 80°C and the drying time is 24h;

[0018] Step 1.5, granulating and tableting the Sr3Al2O6 fine powder after the powder is refined to prepare Sr3Al2O6 shaped discs;

[0019] Step 1.6: sinter the Sr3Al2O6 formed disc in an air atmosphere at a sintering temperature of 1400°C for 4 hours to prepare a Sr3Al2O6 ceramic target.

[0020] Optionally, in the preparation method of the flexible sensor based on the oxide wrinkle structure as described above, when granulating and tableting the Sr3Al2O6 fine powder after the powder is refined in step 1.5, 10% polyvinyl alcohol adhesive is used, and the particle diameter of the Sr3Al2O6 fine powder after granulation is between 0.11-0.18 mm; the diameter of the prepared Sr3Al2O6 molded disc is 30 mm and the thickness is 5 mm.

[0021] Optionally, in the method for preparing a flexible sensor based on an oxide wrinkle structure as described above, step 2 comprises:

[0022] Step 2.1, accurately weigh BaCO3 powder and TiO2 powder according to the molar ratio of Ba to Ti element of 1:1 as raw material 2;

[0023] Step 2.2, weighing ball stone and alcohol according to the mass ratio of raw material 2: ball stone: alcohol = 1:2:2, mixing, ball milling, and sieving, placing the sieved mixed solution in a constant temperature drying oven for drying, to prepare a uniformly mixed powder raw material 2; wherein the drying temperature is 80°C, and the drying time is 24h;

[0024] Step 2.3, putting the raw material 2 mixed with the powder into a crucible, and calcining it in an air atmosphere to synthesize BaTiO3 powder; wherein the calcination temperature is 1000°C and the holding time is 2h;

[0025] Step 2.4, accurately weighing the BaTiO3 powder and La2O3 powder as raw material 3 according to the molar ratio of Ba to La element of 100:3;

[0026] Step 2.5, weighing ball stone and alcohol according to the mass ratio of raw material 3: ball stone: alcohol = 1:2:2, mixing, ball milling, and sieving, placing the sieved mixed solution in a constant temperature drying oven for drying, to prepare a raw material 3 with uniform powder mixing; wherein the drying temperature is 80°C and the drying time is 24h;

[0027] Step 2.6, granulating and tableting the raw material 3 with the powder mixed evenly to prepare a shaped round tablet of the raw material 3;

[0028] Step 2.7, placing the raw material 3 formed disc in an atmosphere furnace, and sintering to obtain a La-BaTiO3 ceramic target; wherein the sintering atmosphere is hydrogen, the sintering temperature is 1200°C, and the temperature is kept for 2 hours.

[0029] Optionally, in the method for preparing a flexible sensor based on an oxide wrinkle structure as described above, step 3 comprises:

[0030] Step 3.1, using pulsed laser deposition technology, on a SrTiO3 single crystal substrate with a crystal orientation of (100), using the Sr3Al2O6 ceramic target prepared in step 1 to prepare a "Sr3Al2O6 / SrTiO3" heterostructure; wherein the temperature of the SrTiO3 single crystal substrate is 800°C, and the distance between the Sr3Al2O6 target and the SrTiO3 single crystal substrate is 6 cm;

[0031] Step 3.2, using pulsed laser deposition technology, on the "Sr3Al2O6 / SrTiO3" heterostructure, the La-BaTiO3 ceramic target is prepared using the step 2 to prepare the "La-BaTiO3 / Sr3Al2O6 / SrTiO3" heterostructure; wherein the temperature of the SrTiO3 single crystal substrate is 800°C, and the distance between the La-BaTiO3 target and the SrTiO3 single crystal substrate is 6 cm.

[0032] Optionally, in the method for preparing a flexible sensor based on an oxide wrinkle structure as described above, in the process of preparing the "Sr3Al2O6 / SrTiO3" heterostructure by pulsed laser deposition technology in step 3.1, the laser energy is 2 J / cm 2 , laser frequency is 3 Hz, oxygen partial pressure is 15 Pa, and growth time is 5 min.

[0033] Optionally, in the process of preparing the "La-BaTiO3 / Sr3Al2O6 / SrTiO3" heterostructure by pulsed laser deposition technology in step 3.2, the laser energy is 2J / cm 2 , laser frequency is 3 Hz, nitrogen partial pressure is 15 Pa, and growth time is 5 min.

[0034] Optionally, in the method for preparing a flexible sensor based on an oxide wrinkle structure as described above, step 4 comprises:

[0035] Step 4.1, attaching the PDMS film to the surface of the La-BaTiO3 layer of the "La-BaTiO3 / Sr3Al2O6 / SrTiO3" heterostructure by electrostatic adsorption to obtain a "PDMS / La-BaTiO3 / Sr3Al2O6 / SrTiO3" heterostructure;

[0036] Step 4.2, place the "PDMS / La-BaTiO3 / Sr3Al2O6 / SrTiO3" heterostructure in deionized water and let it stand for 24 hours to dissolve the Sr3Al2O6 film, remove the obtained "La-BaTiO3 / PDMS" heterostructure from the deionized water and dry it at 60°C for 30 minutes, and finally obtain the "La-BaTiO3 / PDMS" heterostructure.

[0037] Optionally, in the method for preparing a flexible sensor based on an oxide wrinkle structure as described above, the thickness of the PDMS film in step 4.1 is 50 μm; and when the PDMS film is attached by electrostatic adsorption, a tensile stress of 5% is applied to the PDMS film.

[0038] Optionally, in the preparation method of the flexible sensor based on the oxide wrinkle structure as described above, the thickness of the Au electrode grown on the "La-BaTiO3 / PDMS" heterostructure with the wrinkle structure in step 5 is 50 nm, and the test area of ​​the Au electrode is 100 μm×100 μm.

[0039] In a second aspect, an embodiment of the present invention further provides a flexible sensor based on an oxide wrinkle structure, wherein the flexible sensor is prepared by using the method for preparing a flexible sensor based on an oxide wrinkle structure as described in any one of the above items; the flexible sensor comprises: a PDMS encapsulation layer, an Au electrode layer, and a La-BaTiO3 active layer;

[0040] The flexible sensor is arranged in the following order from top to bottom: a PDMS packaging layer, an Au electrode layer, a La-BaTiO3 active layer and a PDMS packaging layer.

[0041] Optionally, in the flexible sensor based on the oxide wrinkle structure as described above, the La-BaTiO3 active layer is a wrinkle structure; the test area of ​​the positive and negative electrodes in the Au electrode layer is 100μm×100μm; and the positive and negative electrodes of the Au electrode layer are used to measure the surface resistance of the wrinkle structure La-BaTiO3 active layer.

[0042] Beneficial effects of the present invention: The present invention provides a flexible sensor based on an oxide wrinkle structure and a preparation method thereof, the preparation method comprising: preparing a Sr3Al2O6 ceramic target by a solid phase method; preparing a La 3+ The ion-doped BaTiO3 ceramic target is a La-BaTiO3 ceramic target; a pulsed laser deposition technique is used on a SrTiO3 single crystal substrate with a crystal orientation of (100) according to the Sr3Al2O6 ceramic target and the La - BaTiO3 ceramic target material is used to prepare a "La-BaTiO3 / Sr3Al2O6 / SrTiO3" heterostructure; a PDMS film is electrostatically adsorbed on the "La-BaTiO3 / Sr3Al2O6 / SrTiO3" heterostructure by a water-soluble method, and the La-BaTiO3 film in the "La-BaTiO3 / Sr3Al2O6 / SrTiO3" heterostructure is peeled off, and a "La-BaTiO3 / Sr3Al2O6 / SrTiO3" heterostructure with a folded structure is prepared. The invention discloses a piezoresistive sensor of a "PDMS / Au / La-BaTiO3 / PDMS" heterostructure; an Au electrode is grown on the "La-BaTiO3 / PDMS" heterostructure with a wrinkled structure by magnetron sputtering to prepare an "Au / La-BaTiO3 / PDMS" heterostructure; another PDMS film is attached to the surface of the Au electrode of the "Au / La-BaTiO3 / PDMS" heterostructure by electrostatic adsorption for encapsulation to prepare a piezoresistive sensor of a "PDMS / Au / La-BaTiO3 / PDMS" heterostructure. The preparation method has high process controllability and simple preparation process. The prepared flexible piezoresistive sensor has the characteristics of high precision, high sensitivity and high reliability. The flexible piezoresistive sensor can adapt to changes in various surfaces and shapes and has a wide range of applications.

[0043] The flexible sensor based on the oxide wrinkle structure provided by the embodiment of the present invention is prepared by any of the preparation methods of the flexible sensor based on the oxide wrinkle structure described above, and the flexible sensor includes: a PDMS encapsulation layer, an Au electrode layer, and a La-BaTiO3 active layer; wherein, the flexible sensor is arranged in order from top to bottom as follows: a PDMS encapsulation layer, an Au electrode layer, a La-BaTiO3 active layer and a PDMS encapsulation layer; the sensor can adapt to changes in various surfaces and shapes, has a wide range of applicability, can be applied to applications requiring compact design, and has the characteristics of high precision and high sensitivity. BRIEF DESCRIPTION OF THE DRAWINGS

[0044] The accompanying drawings are used to provide a further understanding of the technical solution of the present invention and constitute a part of the specification. Together with the embodiments of the present application, they are used to explain the technical solution of the present invention and do not constitute a limitation on the technical solution of the present invention.

[0045] Figure 1 A structural front view of a flexible sensor prepared by the method for preparing a flexible sensor based on an oxide wrinkle structure provided by an embodiment of the present invention;

[0046] Figure 2 A top view of the structure of a flexible sensor prepared by the method for preparing a flexible sensor based on an oxide wrinkle structure provided by an embodiment of the present invention;

[0047] Figure 3 A schematic diagram of the change in resistance of a flexible sensor prepared by the method for preparing a flexible sensor based on an oxide wrinkle structure provided in an embodiment of the present invention when a pressure of 0.001N is applied multiple times. DETAILED DESCRIPTION

[0048] In order to make the purpose, technical solution and advantages of the present invention more clear, the embodiments of the present invention will be described in detail with reference to the accompanying drawings. It should be noted that the embodiments and features in the embodiments of the present application can be combined with each other arbitrarily without conflict.

[0049] The following is a schematic illustration of the implementation of the flexible sensor based on the oxide wrinkle structure and the preparation method thereof provided by the present invention through several specific embodiments.

[0050] Embodiment 1

[0051] The present invention provides a method for preparing a flexible sensor based on an oxide wrinkle structure, the method comprising the following steps:

[0052] Step 101: Prepare Sr3Al2O6 ceramic target material by solid phase method. The specific process is as follows:

[0053] Step 101-1, accurately weighing SrCO3 powder and Al2O3 powder according to the molar ratio of Sr to Al element of 3:2 as raw material 1;

[0054] Step 101-2, weighing ball stone and alcohol according to the mass ratio of raw material 1: ball stone: alcohol = 1:2:2, placing the raw material 1, ball stone and alcohol in a polytetrafluoroethylene ball mill at a speed of 300r / min for 4h, after the ball milling is completed, placing the mixed liquid after the ball stone in the ball mill is sieved in a constant temperature drying oven for drying, the drying temperature is 80°C, and the drying time is 24h, to prepare a uniformly mixed powder raw material 1;

[0055] Step 101-3, putting the raw material 1 with uniform powder mixture into a crucible, calcining in an air atmosphere at a calcination temperature of 1200° C. for a holding time of 4 h, and synthesizing Sr3Al2O6 powder;

[0056] Step 101-4, weighing ball stone and alcohol in a mass ratio of Sr3Al2O6 powder: ball stone: alcohol = 1:2:2, placing Sr3Al2O6 powder, ball stone and alcohol in a polytetrafluoroethylene ball mill at a speed of 300 r / min for 4 hours, after the ball milling is completed, taking out the mixed liquid after the ball stone is sieved in the ball mill and placing it in a constant temperature drying oven for drying at a drying temperature of 80°C and a drying time of 24 hours, to prepare Sr3Al2O6 fine powder after powder refinement;

[0057] Step 101-5, placing Sr3Al2O6 fine powder in an agate mortar, and adding 10% polyvinyl alcohol binder for granulation, wherein the diameter of the granules after granulation is in the range of 0.11-0.18 mm;

[0058] Step 101-6, placing the granulated Sr3Al2O6 particles in a powder tablet press and pressing them into discs with a diameter of 30 mm and a thickness of 5 mm at a molding pressure of 10 MPa;

[0059] Step 101-7, sintering the formed disc with a diameter of 30 mm and a thickness of 5 mm in an air atmosphere at a sintering temperature of 1400° C. for 4 hours to prepare a Sr3Al2O6 ceramic target.

[0060] In the above step 101 of this embodiment, on the one hand, the Sr3Al2O6 target material, as a ceramic material, can react chemically with water, and the reaction process does not require catalysts such as strong acids and strong bases, so the reaction is environmentally friendly and simple. On the other hand, when the Sr3Al2O6 ceramic target material is prepared by the solid phase method in this technical solution, since solid particles such as SrCO3 powder, Al2O3 powder, etc. are used in the reaction process, the purity of the product can be controlled by adjusting the reaction temperature and time, the reaction by-products can be reduced, and it is more economical than some other advanced preparation methods.

[0061] Step 102: Prepare La by solid phase method 3+ Ion-doped BaTiO3 ceramic target is La-BaTiO3 ceramic target. The specific process is as follows:

[0062] Step 102-1, accurately weighing BaCO3 powder and TiO2 powder according to the molar ratio of Ba to Ti element of 1:1 as raw material 2;

[0063] Step 102-2, weighing ball stone and alcohol according to the mass ratio of raw material 2: ball stone: alcohol = 1:2:2, placing raw material 2, ball stone and alcohol in a polytetrafluoroethylene ball mill at a speed of 300r / min for 4h, after the ball milling is completed, placing the mixed liquid after the ball stone in the ball mill is sieved in a constant temperature drying oven for drying, the drying temperature is 80°C, and the drying time is 24h, to prepare a uniformly mixed powder raw material 2;

[0064] Step 102-3, putting the raw material 2 mixed with powder into a crucible, calcining in an air atmosphere at a calcination temperature of 1000° C. for a holding time of 2 h, and synthesizing BaTiO3 powder;

[0065] Step 102-4, accurately weighing BaTiO3 powder and La2O3 powder according to the molar ratio of Ba to La element of 100:3 as raw material 3;

[0066] Step 102-5, weighing ball stone and alcohol according to the mass ratio of raw material 3: ball stone: alcohol = 1:2:2, placing raw material 3, ball stone and alcohol in a polytetrafluoroethylene ball mill at a speed of 300r / min for 4h, after the ball milling is completed, placing the mixed liquid after the ball stone in the ball mill is sieved in a constant temperature drying oven for drying, the drying temperature is 80°C, and the drying time is 24h, to prepare a uniformly mixed powder raw material 3;

[0067] Step 102-6, placing the uniformly mixed raw material 3 in an agate mortar, and adding 10% polyvinyl alcohol binder to granulate the particles, wherein the diameter of the particles after granulation is within the range of 0.11-0.18 mm;

[0068] Step 102-7, placing the granulated raw material 3 in a powder tablet press to press into a disc with a diameter of 30 mm and a thickness of 5 mm, with a molding pressure of 10 MPa;

[0069] Step 102-8, sintering the formed disc with a diameter of 30 mm and a thickness of 5 mm in a hydrogen atmosphere at a sintering temperature of 1200° C. for 2 hours to prepare a La-BaTiO3 ceramic target.

[0070] In the above step 102 of this embodiment, the La-BaTiO3 ceramic target material is a perovskite structure semiconductor, which has a lattice constant similar to that of Sr3Al2O6 and semiconductor resistive switching characteristics brought about by oxygen vacancies.

[0071] Furthermore, in the above steps 102-4 to 102-8 of this embodiment, La 3+ Ion doping into BaTiO3 powder, La2O3 as a dopant can adjust the resistance characteristics of BaTiO3 ceramic target, such as increasing the content of oxygen vacancies in BaTiO3 crystals, thereby improving the conductivity of BaTiO3 ceramic target. It should be noted that in the embodiment of the present invention, the powder mixing of Ba and La elements in a molar ratio of 100:3 is a preferred embodiment; the feasible ratio can be 100:3 to 100:10.

[0072] Step 103: Using pulsed laser deposition technology, on a SrTiO3 single crystal substrate with a crystal orientation of (100), a "La-BaTiO3 / Sr3Al2O6 / SrTiO3" heterostructure is prepared by using pulsed laser deposition technology. The specific process is as follows:

[0073] Step 103-1, using pulsed laser deposition technology, grow a 20nm thick Sr3Al2O6 film on a SrTiO3 single crystal substrate with a crystal orientation of (100). The target material used is the Sr3Al2O6 ceramic target prepared in the above steps, the temperature of the SrTiO3 single crystal substrate is 800°C, the distance between the Sr3Al2O6 target and the SrTiO3 single crystal substrate is 6cm, and the laser energy is 2J / cm 2 , the laser frequency is 3Hz, the oxygen partial pressure is 15Pa, and the growth time is 5min, and the "Sr3Al2O6 / SrTiO3" heterostructure is prepared;

[0074] Step 103-2: Use pulsed laser deposition technology to grow a 20nm thick La-BaTiO3 film on the "Sr3Al2O6 / SrTiO3" heterostructure. The target material used is the La-BaTiO3 ceramic target prepared in the previous step, the temperature of the SrTiO3 single crystal substrate is 800°C, the distance between the La-BaTiO3 target and the SrTiO3 single crystal substrate is 6cm, and the laser energy is 2J / cm 2 , laser frequency was 3 Hz, nitrogen pressure was 15 Pa, growth time was 5 min, and the “La-BaTiO3 / Sr3Al2O6 / SrTiO3” heterostructure was prepared.

[0075] In the above step 103 of the present embodiment, when the pulsed laser deposition technology is used to prepare the "La-BaTiO3 / Sr3Al2O6 / SrTiO3" heterostructure, the technology can ensure that the prepared film has good crystallinity and high density. Since the deposition materials of the heterostructure are directly derived from the Sr3Al2O6 ceramic target and the La-BaTiO3 target, the introduction of impurity-free materials can ensure a high degree of consistency between the film composition and the target composition. In addition, the growth process of the film is precisely controlled by controlling the laser energy, frequency and deposition environment (atmosphere and atmosphere pressure). This controllability can finely adjust the thickness, morphology, grain size, etc. of the film.

[0076] Step 104: Using a water-soluble method, the PDMS film is electrostatically adsorbed on the "La-BaTiO3 / Sr3Al2O6 / SrTiO3" heterostructure and the La-BaTiO3 film in the "La-BaTiO3 / Sr3Al2O6 / SrTiO3" heterostructure is peeled off to prepare a "La-BaTiO3 / PDMS" heterostructure with a wrinkled structure. The detailed process is described as follows:

[0077] Step 104-1, applying 5% tensile stress to a 50 μm thick PDMS film and attaching it to the surface of the La-BaTiO3 layer of the "La-BaTiO3 / Sr3Al2O6 / SrTiO3" heterostructure by electrostatic adsorption to obtain a "PDMS / La-BaTiO3 / Sr3Al2O6 / SrTiO3" heterostructure;

[0078] Step 104-2, place the "PDMS / La-BaTiO3 / Sr3Al2O6 / SrTiO3" heterostructure in deionized water and let it stand for 24 hours to dissolve the Sr3Al2O6 film, remove the obtained "La-BaTiO3 / PDMS" heterostructure from the deionized water and dry it at 60°C for 30 minutes, and finally obtain the "La-BaTiO3 / PDMS" heterostructure.

[0079] It should be understood that when the Sr3Al2O6 film is dissolved in deionized water, the Sr3Al2O6 film adheres to the SrTiO3 substrate, so the SrTiO3 substrate is peeled off from the "PDMS / La-BaTiO3 / Sr3Al2O6 / SrTiO3" heterostructure along with the Sr3Al2O6 film; when the Sr3Al2O6 film is dissolved in deionized water, the tensile stress of the PDMS film is released in the deionized water, which causes the La-BaTiO3 film to present a wrinkled structure due to the release of the tensile stress. For easier understanding, please refer to the attached Figure 1 Indicated in Figure 1 The structural front view of the flexible sensor prepared by the preparation method of the flexible sensor based on the oxide wrinkle structure; Figure 1 As shown, the La-BaTiO3 active layer can show the folded structure; in this embodiment, the folded structure of the La-BaTiO3 film is used as the oxide-based semiconductor active layer. Due to the characteristics of its own folded structure and the variable expansion and contraction of the La-BaTiO3 film, it can meet the flexible application requirements of the piezoresistive sensor. Since the folded structure of the La-BaTiO3 active layer is described in detail here, Figure 1The gold electrode and PDMS encapsulation layer in the step 104 can be referred to the description of the subsequent steps. Further, in step 104, the "La-BaTiO3 / PDMS" heterostructure is prepared by a water-soluble method, which is relatively simple to operate, has relatively mild reaction conditions, and has strong controllability.

[0080] Step 105: grow a gold Au electrode on the "PDMS / La-BaTiO3" heterostructure with a wrinkled structure by magnetron sputtering to prepare an "Au / La-BaTiO3 / PDMS" heterostructure. The specific process is as follows:

[0081] The metal mask with the hollowed-out electrode pattern is fixed on the surface of the La-BaTiO3 film, and then placed in a magnetron sputtering instrument to grow a 50nm thick Au electrode. Finally, the metal mask is removed from the surface of the La-BaTiO3 film to obtain the "Au / La-BaTiO3 / PDMS" heterostructure with a specific electrode pattern. The test area of ​​the Au electrode is 100μm×100μm.

[0082] It should be understood that the role of the above Au electrode in the "La-BaTiO3 / PDMS" heterostructure is that the 50nm thick Au film ensures the conductivity of the current transport layer without affecting the flexibility of the sensor. The reliability of the flexible sensor is ensured by rationally designing the thickness of the Au electrode and the test area in the flexible sensor.

[0083] Step 106: attach another 50 μm thick PDMS film to the surface of the Au electrode by electrostatic adsorption for packaging, and obtain a piezoresistive sensor with a "PDMS / Au / La-BaTiO3 / PDMS" heterostructure.

[0084] In order to facilitate the understanding of the "PDMS / Au / La-BaTiO3 / PDMS" heterostructure prepared in the embodiment of the present invention, please refer to the attached Figure 1 and attached Figure 2 Attached Figure 1 and attached Figure 2 Schematic diagram of the piezoresistive sensor of the "PDMS / La-BaTiO3 / Au / PDMS" heterostructure observed from different angles. Figure 1 The front view of the structure of the flexible sensor prepared by the preparation method of the flexible sensor based on the oxide wrinkle structure, and the attached Figure 2 This is a top view of the structure of a flexible sensor prepared by the method for preparing a flexible sensor based on an oxide wrinkle structure.

[0085] like Figure 1As shown in the figure, the "PDMS / Au / La-BaTiO3 / PDMS" piezoresistive sensor is a multi-layer structure composed of different materials. From the order of the structural presentation of each layer:

[0086] First, the La-BaTiO3 active layer with a pleated structure is used as an oxide-based semiconductor active layer and is arranged in the middle layer position of the above-mentioned multilayer piezoresistive sensor. The pleated La-BaTiO3 active layer is a soft material that can adapt to changes in various surfaces and shapes in a complex working environment. Since the pleated La-BaTiO3 active layer is a flexible material with piezoresistive properties, its own resistance value can change significantly when subjected to external force. Secondly, an Au electrode layer is provided on one side of the La-BaTiO3 active layer with a pleated structure, and the electrode layer is composed of positive and negative Au electrodes. The Au electrode layer serves as a resistance sensing layer, which can measure the resistance change of the pleated La-BaTiO3 active layer in the test area and convert the resistance before and after the change into a voltage or current signal. Finally, the PDMS layer is provided as an encapsulation layer on the outermost side of the above-mentioned piezoresistive sensor to provide protection support and pressure conduction for the piezoresistive sensor as a whole.

[0087] like Figure 2 As shown in the attached Figure 2 From the top view of the flexible piezoresistive sensor, the PDMS layer is the outermost layer of the piezoresistive sensor layer structure. Since the PDMS layer prepared in the embodiment of the present invention is 50 μm thick, the PDMS layer has good transparency. The highly transparent PDMS layer allows the internal Au electrode layer and the wrinkled La-BaTiO3 active layer to be directly seen from the top view. Figure 2 In the figure, the test area (100 μm×100 μm) located between the positive and negative Au electrodes can also be directly observed. It should be understood that the test area is the wrinkled La-BaTiO3 active layer located between the positive and negative Au electrodes.

[0088] In this embodiment, the positive and negative Au electrodes measure the surface resistance of the test area of ​​the wrinkled La-BaTiO3 active layer. Surface resistance refers to the resistance value per unit area on the surface of a material. Since surface resistance can detect small pressure changes, it can be applied to piezoresistive sensors with high sensitivity requirements. Of course, the flexible resistance sensor of the embodiment of the present invention also adjusts the position of the positive and negative Au electrodes to test the corresponding body resistance (adjust the positive and negative Au electrodes to Figure 1The positive and negative Au electrodes are arranged opposite to each other on the two sides of the La-BaTiO3 active layer at the PDMS layer on different sides of the La-BaTiO3 active layer). Bulk resistance refers to the resistance value per unit volume inside the material. Generally, the change in surface resistance is often more significant than the change in bulk resistance at the same pressure (when the thickness of the La-BaTiO3 active layer is low, the resistance change caused by external force deformation near the surface of the material is usually larger than that inside the material). The change in surface resistance can better reflect the local deformation, so the piezoresistive sensor can detect more subtle spatial changes, and the resistance change is easier to measure.

[0089] As an optional implementation, the piezoresistive sensor of the embodiment of the present invention preferably selects the aforementioned surface resistance testing method.

[0090] In order to verify the performance of the flexible sensor based on the oxide wrinkle structure prepared in the embodiment of the present invention, the prepared flexible sensor was subjected to a performance verification experiment. Figure 3 The hint, Figure 3 A schematic diagram of the change in resistance of the flexible sensor provided by an embodiment of the present invention when a pressure of 0.001 N is applied multiple times. As shown in the figure, when a pressure of 0.001 N is applied to the flexible sensor at a preset frequency, the resistance value inside the sensor shows a periodic change, and its resistance value changes significantly compared to the initial state, indicating that the sensor exhibits good sensitivity and cyclic stability.

[0091] Here, the working principle of the flexible sensor based on the oxide wrinkle structure prepared in the embodiment of the invention is introduced in detail: when a pressure of 0.001N is applied to the flexible sensor, the PDMS encapsulation layer is deformed by the external pressure, which in turn affects the expansion and contraction of the wrinkled structure of the La-BaTiO3 active layer. When the La-BaTiO3 active layer with a wrinkled structure itself undergoes expansion and contraction changes, its own resistance value also changes accordingly; the positive and negative Au electrodes on one side of the La-BaTiO3 active layer serve as resistance sensing layers, and then measure the resistance change of the wrinkled La-BaTiO3 active layer in the test area, and convert the resistance before and after the change into a voltage or current signal.

[0092] From the perspective of device preparation, the flexible sensor based on the oxide wrinkle structure of the embodiment of the present invention adopts solid particles such as SrCO3 powder, Al2O3 powder, BaCO3 powder, TiO2 powder and La2O3 powder in the selection of raw materials, and its reaction process is highly controllable. From the perspective of the prepared flexible sensor, the flexible piezoresistive sensor has high precision, high sensitivity and high reliability; the flexible piezoresistive sensor can adapt to changes in various surfaces and shapes and has a wide range of applications, such as electronic skin. Since the La-BaTiO3 oxide wrinkle structure is designed as a thin layer material, it can reduce the overall weight of the piezoresistive sensor, making the device lightweight and portable, and therefore can be used in applications that require a compact design.

[0093] Embodiment 2

[0094] The embodiment of the present invention provides a flexible sensor based on an oxide wrinkle structure, the flexible sensor comprising: a PDMS encapsulation layer, an Au electrode layer, and a La-BaTiO3 active layer; wherein the flexible sensor is sequentially arranged from top to bottom as: a PDMS encapsulation layer, an Au electrode layer, a La / BaTiO3 active layer, and a PDMS encapsulation layer;

[0095] Furthermore, the La-BaTiO3 active layer is a wrinkled structure, and the test area of ​​the positive and negative electrodes in the Au electrode layer is 100 μm×100 μm; and the positive and negative electrodes of the Au electrode layer are used to measure the surface resistance of the wrinkled structure La-BaTiO3 active layer;

[0096] In an optional implementation, the thickness of the PDMS encapsulation layer is 50 μm. In the embodiment of the present invention, the PDMS layer is used as an encapsulation layer and is disposed on the outermost side of the flexible piezoresistive sensor to provide protection support and pressure conduction for the entire piezoresistive sensor.

[0097] In an optional implementation, the Au electrode layer is a 50 nm thick film. In the embodiment of the present invention, the thickness of the Au electrode layer is set to 50 nm, which ensures the conductivity of the current transport layer and does not affect the flexibility of the sensor.

[0098] The flexible sensor based on the oxide wrinkle structure of the embodiment of the present invention can be obtained according to the preparation method provided in the first embodiment, and its working principle is: when an external force is applied to the flexible sensor, the PDMS encapsulation layer is deformed by the external pressure, thereby affecting the expansion and contraction of the wrinkle-shaped structure of the La-BaTiO3 active layer. When the wrinkle-shaped La-BaTiO3 active layer itself undergoes expansion and contraction changes, its own resistance value also changes accordingly; the positive and negative Au electrodes on one side of the La-BaTiO3 active layer serve as resistance sensing layers, and then measure the resistance change of the wrinkled La-BaTiO3 active layer in the test area, and convert the resistance before and after the change into a voltage or current signal.

[0099] The flexible sensor based on the oxide wrinkle structure of the embodiment of the present invention has the characteristics of high precision, high sensitivity and high reliability; the flexible piezoresistive sensor can adapt to changes in various surfaces and shapes, has a wide range of applications, and can be used in applications requiring compact design.

[0100] Although the embodiments disclosed in the present invention are as above, the contents are only embodiments adopted to facilitate understanding of the present invention and are not intended to limit the present invention. Any technician in the field to which the present invention belongs can make any modifications and changes in the form and details of implementation without departing from the spirit and scope disclosed in the present invention, but the patent protection scope of the present invention shall still be subject to the scope defined in the attached claims.

Claims

1. A method for preparing a flexible sensor based on an oxide wrinkle structure, characterized in that: The preparation method is carried out according to the following steps: Step 1: Prepare Sr3Al2O6 ceramic target by solid phase method; Step 2: Prepare La using solid phase method 3+ Ion-doped BaTiO3 ceramic target, namely La-BaTiO3 ceramic target; Step 3: Using pulsed laser deposition technology, on a SrTiO3 single crystal substrate with a (100) orientation, a "La-BaTiO3 / Sr3Al2O6 / SrTiO3" heterostructure is prepared according to the Sr3Al2O6 ceramic target and the La-BaTiO3 ceramic target; Step 4: electrostatically adsorbing a polydimethylsiloxane (PDMS) film onto the "La-BaTiO3 / Sr3Al2O6 / SrTiO3" heterostructure by a water-soluble method, peeling off the La-BaTiO3 film in the "La-BaTiO3 / Sr3Al2O6 / SrTiO3" heterostructure, and preparing a "La-BaTiO3 / PDMS" heterostructure with a wrinkled structure; Step 5, growing a gold Au electrode on the "La-BaTiO3 / PDMS" heterostructure with a wrinkled structure by a magnetron sputtering method, to prepare an "Au / La-BaTiO3 / PDMS" heterostructure; Step 6: attach another PDMS film to the Au electrode surface of the "Au / La-BaTiO3 / PDMS" heterostructure by electrostatic adsorption to encapsulate it, so as to obtain a piezoresistive sensor of the "PDMS / Au / La-BaTiO3 / PDMS" heterostructure.

2. The method for preparing a flexible sensor based on an oxide wrinkle structure according to claim 1, characterized in that: The step 1 comprises: Step 1.1, accurately weigh SrCO3 powder and Al2O3 powder according to the molar ratio of Sr to Al element of 3:2 as raw material 1; Step 1.2, weighing ball stone and alcohol according to the mass ratio of raw material 1: ball stone: alcohol = 1:2:2, mixing, ball milling, and sieving, placing the sieved mixed liquid in a constant temperature drying oven for drying, and preparing a raw material 1 with uniform powder mixing; wherein the drying temperature is 80°C and the drying time is 24h; Step 1.3, putting the raw material 1 mixed with the powder into a crucible, and calcining it in an air atmosphere to synthesize Sr3Al2O6 powder; wherein the calcination temperature is 1200°C and the holding time is 4h; Step 1.4, according to the mass ratio of Sr3Al2O6 powder: ball stone: alcohol = 1:2:2, weigh the ball stone and alcohol, mix, ball mill, and sieve, and place the sieved mixed solution in a constant temperature drying oven for drying to prepare Sr3Al2O6 fine powder after powder refinement; wherein the drying temperature is 80°C and the drying time is 24h; Step 1.5, granulating and tableting the Sr3Al2O6 fine powder after the powder is refined to prepare Sr3Al2O6 shaped discs; Step 1.6: sinter the Sr3Al2O6 formed disc in an air atmosphere at a sintering temperature of 1400°C for 4 hours to prepare a Sr3Al2O6 ceramic target.

3. The method for preparing a flexible sensor based on an oxide wrinkle structure according to claim 2, characterized in that: In the step 1.5, when the Sr3Al2O6 fine powder after the powder is refined is granulated and tableted, 10% polyvinyl alcohol adhesive is used, and the particle diameter of the Sr3Al2O6 fine powder after granulation is between 0.11-0.18mm; the diameter of the prepared Sr3Al2O6 molded disc is 30mm and the thickness is 5mm.

4. The method for preparing a flexible sensor based on an oxide wrinkle structure according to claim 1, characterized in that: The step 2 comprises: Step 2.1, accurately weigh BaCO3 powder and TiO2 powder according to the molar ratio of Ba to Ti element of 1:1 as raw material 2; Step 2.2, weighing ball stone and alcohol according to the mass ratio of raw material 2: ball stone: alcohol = 1:2:2, mixing, ball milling, and sieving, placing the sieved mixed solution in a constant temperature drying oven for drying, to prepare a uniformly mixed powder raw material 2; wherein the drying temperature is 80°C, and the drying time is 24h; Step 2.3, putting the raw material 2 mixed with the powder into a crucible, and calcining in an air atmosphere to synthesize BaTiO3 powder; wherein the calcination temperature is 1000°C and the holding time is 2h; Step 2.4, accurately weighing the BaTiO3 powder and La2O3 powder as raw material 3 according to the molar ratio of Ba to La element of 100:3; Step 2.5, weighing ball stone and alcohol according to the mass ratio of raw material 3: ball stone: alcohol = 1:2:2, mixing, ball milling, and sieving, placing the sieved mixed solution in a constant temperature drying oven for drying, to prepare a raw material 3 with uniform powder mixing; wherein the drying temperature is 80°C and the drying time is 24h; Step 2.6, granulating and tableting the raw material 3 with the powder mixed evenly to prepare a shaped round tablet of the raw material 3; Step 2.7, placing the raw material 3 formed disc in an atmosphere furnace and sintering to obtain a dense La-BaTiO3 ceramic target; wherein the sintering atmosphere is hydrogen, the sintering temperature is 1200°C, and the temperature is kept for 2 hours.

5. The method for preparing a flexible sensor based on an oxide wrinkle structure according to claim 1, characterized in that: The step 3 comprises: Step 3.1, using pulsed laser deposition technology, on a SrTiO3 single crystal substrate with a crystal orientation of (100), using the Sr3Al2O6 ceramic target prepared in step 1 to prepare a "Sr3Al2O6 / SrTiO3" heterostructure; wherein the temperature of the SrTiO3 single crystal substrate is 800°C, and the distance between the Sr3Al2O6 target and the SrTiO3 single crystal substrate is 6 cm; Step 3.2, using pulsed laser deposition technology, on the "Sr3Al2O6 / SrTiO3" heterostructure, the La-BaTiO3 ceramic target is prepared using the step 2 to prepare the "La-BaTiO3 / Sr3Al2O6 / SrTiO3" heterostructure; wherein the temperature of the SrTiO3 single crystal substrate is 800°C, and the distance between the La-BaTiO3 target and the SrTiO3 single crystal substrate is 6 cm.

6. The method for preparing a flexible sensor based on an oxide wrinkle structure according to claim 5, characterized in that: In the process of preparing the "Sr3Al2O6 / SrTiO3" heterostructure by pulsed laser deposition technology in step 3.1, the laser energy is 2J / cm 2 , laser frequency is 3 Hz, oxygen partial pressure is 15 Pa, and growth time is 5 min.

7. The method for preparing a flexible sensor based on an oxide wrinkle structure according to claim 5, characterized in that: In the process of preparing the "La-BaTiO3 / Sr3Al2O6 / SrTiO3" heterostructure by pulsed laser deposition technology in step 3.2, the laser energy is 2J / cm 2 , laser frequency is 3 Hz, nitrogen partial pressure is 15 Pa, and growth time is 5 min.

8. The method for preparing a flexible sensor based on an oxide wrinkle structure according to claim 1, characterized in that: The step 4 comprises: Step 4.1, attaching the PDMS film to the surface of the La-BaTiO3 layer of the "La-BaTiO3 / Sr3Al2O6 / SrTiO3" heterostructure by electrostatic adsorption to obtain the "PDMS / La-BaTiO3 / Sr3Al2O6 / SrTiO3" heterostructure; Step 4.2, place the "PDMS / La-BaTiO3 / Sr3Al2O6 / SrTiO3" heterostructure in deionized water and let it stand for 24 hours to dissolve the Sr3Al2O6 film, remove the obtained "La-BaTiO3 / PDMS" heterostructure from the deionized water and dry it at 60°C for 30 minutes, and finally obtain the "La-BaTiO3 / PDMS" heterostructure.

9. The method for preparing a flexible sensor based on an oxide wrinkle structure according to claim 8, characterized in that: The thickness of the PDMS film in step 4.1 is 50 μm; when the PDMS film is attached by electrostatic adsorption, a tensile stress of 5% is applied to the PDMS film.

10. The method for preparing a flexible sensor based on an oxide wrinkle structure according to any one of claims 1 to 9, characterized in that: In the step 5, the thickness of the Au electrode grown on the "La-BaTiO3 / PDMS" heterostructure with a wrinkled structure is 50 nm, and the test region of the Au electrode has an area of ​​100 μm×100 μm.

11. A flexible sensor based on an oxide wrinkle structure, characterized in that: A flexible sensor based on an oxide wrinkle structure is prepared by the preparation method according to any one of claims 1 to 10; the flexible sensor comprises: a PDMS encapsulation layer, an Au electrode layer, and a La-BaTiO3 active layer; The flexible sensor is arranged in the following order from top to bottom: a PDMS packaging layer, an Au electrode layer, a La-BaTiO3 active layer and a PDMS packaging layer.

12. The flexible sensor based on oxide wrinkle structure according to claim 11, characterized in that: The La-BaTiO3 active layer has a wrinkled structure; The test area of ​​the positive and negative electrodes in the Au electrode layer is 100 μm×100 μm; and the positive and negative electrodes in the Au electrode layer are used to measure the surface resistance of the wrinkled structure La-BaTiO3 active layer.

Citation Information

Patent Citations

  • Piezoresistive pressure sensor and preparation method thereof

    CN110243506A

  • Barium titanate / lanthanum nickelate ferroelectric superlattice film material and preparation method thereof

    CN110527952A

  • Preparation method of lanthanum-doped barium titanate target material

    CN112500155A

  • Piezoelectric element

    JP2000277825A

  • Sensor capable of sensing pressure by means of the deformation of a wrinkled piezoelectric layer

    US20160252411A1